Pulsed ENDOR study of Cu(I)-NO adsorption complexes in Cu-L zeolite - Venkatesan, Uma Maheswari; Hartmann, Martin; Pöppl, Andreas (Journal of Physical Chemistry B, 2005)
The local environments of Cu(I)-NO adsorption complexes formed in zeolites Cu-L and Cu-ZSM-5 were studied by electron spin resonance (ESR), pulsed electron nuclear double resonance (ENDOR), and hyperfine sublevel correlation spectroscopy (HYSCORE). Cu(I)-NO complexes have attracted special interest because they are important intermediates in the catalytic decomposition of nitric oxide over copper exchanged zeolites. Recently, detailed structures of the complexes in Cu-ZSM-5 zeolites, O-Al-O-Cu(I)-NO, have been proposed on the basis of quantum chemical calculations (Pietrzyk, et al. J. Phys. Chem. B 2003, 107, 6105. Dědeček, et al. Phys. Chem. Chem. Phys. 2002, 4, 5406). Al pulsed ENDOR and HYSCORE experiments allowed the hyperfine coupling parameters of an aluminum nuclei found in the vicinity of the Cu(I)-NO complex formed in zeolite Cu-L to be estimated. The data indicate that the aluminum atom is located in the third coordination sphere of the adsorbed NO molecule in agreement with the suggested geometry of the adsorption sites. Broad distributions of aluminum nuclear quadrupole and hyperfine coupling parameters and short electron spin relaxation times of the Cu(I)-NO species prevented the determination of the Al hyperfine couplings for zeolite Cu-ZSM-5. © 2005 American Chemical Society.